ショウワ キチ ヨリ ナンイ 75 ド マデ ノ リョコウ オヨビ クック ミサキ ヘノ リョコウ ニオケル ジュウリョク ソクテイ ニツイテ - 大浦, 浩文; オオウラ, ヒロブミ; OURA, Hirobumi (国立極地研究所, 1965)
P(論文) Along the inland traverse route from Syowa Station to location C21 (F451, 74°57'S, 38°27'E) and along the traverce routeon the sea ice in Lutzow-Holm Bay toward the Cook Point, the gravity was measured by Worden Gravimeter in 1961 On the inland traverse, the intervals of the observation stations were 6 km in the range from the coast to point C6 (F158, 71°00'S, 41°00'E), and 12km in the range from C6 to C21 The number of the observation stations on the sea ice of the Lutzow-Holm Bay was seventeen Seven stations of them coincided with the points where the depth was sounded by plummet The error of the measurment seemed to be mainly caused by the abnormal drift of gravimeter Though the carrier (container) of the gravimeter was covered with sheets of foam rubber and set in a wooden box, which was set on a thick sheet of foam rubber and was mounted with rubber bands to the snow car, the gravimeter must have suffered frequent shocks when the snow car passed the group of sastrugi The mean drift of the gravimeter was 0 285mgal/day in the year. But it was smaller in the period of traverse, that is, 0 182 mgal/day in the autumn inland traverse, 0 247 mgal/day in the spring inland traverse and 0 082 mgal/day in the Cook Point traverse The negatue drift was noticed at some camp sites where we stayed for several days The mean error of the measurments estimated from all viewpoints was about 3 5 mgal The results obtained from the inland traverse route are listed in a table with the location ana the height of the observation station, the values of the standard gravity, the free air anomaly, the thickness of ice, the height of bed rock and the distance from Syowa Station along the route The thickness of ice was calculated under three assumptions (1) the Bouguer anomaly is zero, (2) the density of ice is 0 9 g/cm^3, (3) the density of bed rock is 2 67 g/cm^3. Since the seismic sounding by our party was a failure, the Bouguer anomaly could not be calculated But the traverse route of the third expedition party crosses our ...